Environmental protection and human rights / Donald K. Anton, Dinah Shelton. - Anton, Donald K.; Shelton, Dinah (Cambridge University Press, 2011)
With unique scholarly analysis and practical discussion, this book provides a comprehensive introduction to the relationship between environmental protection and human rights being formalized into law in many legal systems. This book instructs on environmental techniques and procedures that assist in the protection of human rights. The text provides cogent guidance on a growing international jurisprudence on the promotion and protection of human rights in relation to the environment that has been developed by international and regional human rights bodies and tribunals. It explores a rich body of case law that continues to develop within states on the environmental dimension of the rights to life, to health, and to public participation and access to information. Five compelling contemporary case studies are included that implicate human rights and the environment, ranging from large dam projects to the creation of a new human right to a clean environment.